Financial Markets and Corporate Reporting under Geopolitical Risks 2022 & 2023 Annual Conference on Finance and Accounting (ACFA), Prague, Czech Republic - Procházka, David (Springer Proceedings in Business and Economics, 2024)
XII, 244 p. 33 illus., 29 illus. in color.